Surfactant-Free w/o Gelled Emulsions with Benzyl Alcohol: Analytical Study for Varnish Removal on Oil Paintings - Marianna Potenza; Silvia Germinario; Stefano Volpin; Elisa Isella; Paolo Cremonesi; Antonella Casoli (Applied Sciences, 2024)
In this study, the use of surfactant-free water-in-oil gelled emulsions containing benzyl alcohol (BAl/w) is proposed as an alternative to the more traditional use of organic solvents for removing varnishes. To mitigate the strong swelling and solvent action of benzyl alcohol and protect the paint and the underlying layers, temporary hydrophobization with cyclomethicone D5 has been proposed. The aim of this study was to evaluate the application of BAl/w surfactant-free, constructed with three different gelling agents of the aqueous dispersing phase (xanthan gum, agar-agar, and polyacrylate) on the surface of an oil painting varnished with and without preliminary saturation with D5. The role of pH, which can influence the ionization, and therefore the water solubility of terpene molecules and all other acid species present on the surface, was also studied. Fourier transform infrared (FT-IR) and Raman spectroscopies were used to characterize the pigments and the surface before and after varnish removal. Elemental analysis and any morphological changes were evaluated using scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS). The leaching efficiency of each surfactant-free emulsion applied on the paint surface was evaluated using a gas chromatography/mass spectroscopy (GC/MS) analysis: the fatty acid content was established in each sample before and after the treatments.